More benefit or harm? Moral contextualism shapes public attitudes towards social egg freezing - Forke, Anna; Siegers, Pascal (Frontiers in Political Science, 2022)
Medical treatments at the beginning as well as at the end of a human life are highly contested in public discourse. This study shows what factors shape the acceptance of social egg freezing (or oocyte cryopreservation) as an assisted reproduction technology (ART). Existing research focused on the social-demographic profile and motivations of persons using oocyte cryopreservation for non-medical reasons. Less work has been published about the public acceptance of social egg freezing. We argue that public attitudes depend on the conditions and individual motivation for the use. Based on the theory of moral contextualism, we deduce potential factors influencing attitudes towards cryopreservation from the literature on medical ethics (for example the number of oocytes used or the age up to which women plan to use the oocytes). We expect that individuals have moral intuitions about the potential harms and benefits of social egg-freezing that influence their attitudes. The influence of these factors on individual attitudes is modelled using a factorial design embedded into a web survey. The results show that factors associated with potential harm to the children decrease acceptance of cryopreservation, whereas factors associated with potential harm to the women increases acceptance. The strongest effect has the age at which women plan to use the preserved oocytes. Individuals having permissive age deadlines for childrearing are overall less critical of social egg-freezing.